2009
DOI: 10.4081/1652
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical localization and quantification of plasma membrane Ca2+-ATPase activity in mollusc digestive gland cells

Abstract: A cytochemical method allowing the localization and quantification of plasma membrane Ca2+- ATPase (PMCA) in frozen sections obtained from digestive gland cells of Mytilus galloprovincialis, Tapes tapes and Chamelea gallina, is presented. The method utilizes lead as a trapping agent of PO4 2- ions released by Ca2+-ATPase activity. The amount of lead sulphide precipitate proportionally related to PMCA activity was quantified by a light microscopy digital imaging analysis system. The optimal assay conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…In these studies, elevated temperature resulted in increased rates of calcification, due to heightened enzyme activity associated with the biomineralization process and consequently raised uptake of Ca 2+ ions (Bevelander and Nakahara, 1969;Pons et al, 2002;Thomsen et al, 2010;Lervik et al, 2013). Although the results from our study showed a difference in response to changing temperatures.…”
Section: Discussioncontrasting
confidence: 48%
“…In these studies, elevated temperature resulted in increased rates of calcification, due to heightened enzyme activity associated with the biomineralization process and consequently raised uptake of Ca 2+ ions (Bevelander and Nakahara, 1969;Pons et al, 2002;Thomsen et al, 2010;Lervik et al, 2013). Although the results from our study showed a difference in response to changing temperatures.…”
Section: Discussioncontrasting
confidence: 48%